Screening for schistosomiasis in a non-endemic setting: Accuracy of a rapid antibody test using finger prick blood - Margherita Ortalli; Bianca Granozzi; Michele Bacchiega; Concettina Di Lillo; Greta Roncarati; Silvia Stefania Longoni; Cristina Mazzi; Elisa Vanino; Zeno Bisoffi; Stefania Varani (Travel Medicine and Infectious Disease)
Human schistosomiasis is a chronic neglected tropical disease caused by blood flukes of the genus Schistosoma, infecting 250 million people worldwide, mostly in sub-Saharan Africa. Recently, thousands of cases have been reported in immigrants to non-endemic countries, including Italy. Serological screening is recommended but so far, no accurate point-of-care (POC) and lab-free test is available.We carried out a prospective evaluation of the accuracy of a new immunochromatographic test (Black- ICT, IgG-IgM) using finger prick blood for screening of schistosomiasis at the University Hospital of Bologna. Eligible immigrants were recruited regardless the presence of symptoms. The other tests used were microscopy on stools and urine, a serum-ICT (SCHISTOSOMA ICT IgG-IgM, LDBIO Diagnostics), an ELISA (NovaLisa Schistosoma mansoni IgG, Novatec) and a Western Blot (SCHISTO II Western Blot IgG, LDBIO Diagnostics). Statistical analysis was performed using a Bayesian latent class model.We enrolled 198 subjects in the study. Black-ICT had a sensitivity of 86.6 % (95 % credible interval 76.9–94.7) and a specificity of 88.4 % (82.0–94.3). At the estimated prevalence level for the study sample, 32.6 % (25.5–40.0), the positive and negative predictive values were 78.2 % (66.4–89.4) and 93.2 % (87.7–97.6), respectively. Good agreement was found with the other antibody tests, with the highest sensitivity being observed for serum-ICT (91.0 %, 84.7–96.4) and the highest specificity for ELISA (92.6 %, 87.5–96.7).The novel POC test for schistosomiasis showed satisfactory results and could improve the detection of this parasitic infection in non-endemic settings, as the lab-free approach could greatly expand the target group.